TEMPOROMANDIBULAR JOINT ARTHROCENTESIS AS A TREATMENT FOR PAIN AND LIMITATION OF MOUTH OPENING: CASE REPORT - Cardoso, Laís Inês Silva (2024)
Temporomandibular disorders encompass joint changes may occur within the temporomandibular joint (TMJ), including those involving anterior displacement of the articular disc, resulting in pain and limited mouth opening. The arthrocentesis technique is effective in treating these symptoms, furthermore being a simple, low-cost and highly predictable technique. The aim of this work is to report the case of a patient with anterior disc displacement without reduction, associated with pain and limited mouth opening, treated with the arthrocentesis technique. Female patient, 28 years old, with facial pattern II, anterior open bite and complaining of “pain and difficulty opening the mouth”. Her initial mouth opening was 20mm, with pain complaint between 7 and 8 on the Visual Pain Scale (EVD). An isolated arthrocentesis technique was performed in both TMJs, under local anesthesia associated with intravenous sedation in the operating room. During the three-month postoperative follow-up, the patient improved mouth opening to 30 mm and pain close to 1 on the EVD. Therefore, the isolated arthrocentesis technique proved be effective in treating symptoms like pain and limited mouth opening in patients diagnosed with anterior displacement of the articular disc without reduction.